2019
DOI: 10.1016/j.addbeh.2019.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Culturally relevant risk and protective factors for nonmedical use of prescription opioids among incarcerated African American men

Abstract: Background: Recent studies have demonstrated that nonmedical use of prescription opioids (NMUPO) is a national phenomenon affecting a multitude of subpopulations, including incarcerated African American men. However, there has been little investigation of the correlates of NMUPO among this population. Objective: Grounded in primary socialization theory, the current study aimed to examine the association between family bonds, family history of prescription drug misuse, and mental health symptoms on NMUPO amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Ultimately, 182 studies met the inclusion criteria; three studies only included event count and not participant sample size [13‐15]. A total of 53 (29%) studies employed cross‐sectional, population‐based and nationally representative observational designs [7,14,16–63]; 13 (7%) employed longitudinal, cohort‐based observational designs [64–76]; 4 (2%) employed case control designs [77–80]; 6 (3%) were randomised control trials [81–86]; 54 (30%) employed cross‐sectional data from convenience samples [72,87–139]; 10 (5%) employed longitudinal (including repeated cross‐sectional) data from nationally representative studies [15,17,140–146]; and 42 (23%) retrospectively assessed individual‐level data […”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, 182 studies met the inclusion criteria; three studies only included event count and not participant sample size [13‐15]. A total of 53 (29%) studies employed cross‐sectional, population‐based and nationally representative observational designs [7,14,16–63]; 13 (7%) employed longitudinal, cohort‐based observational designs [64–76]; 4 (2%) employed case control designs [77–80]; 6 (3%) were randomised control trials [81–86]; 54 (30%) employed cross‐sectional data from convenience samples [72,87–139]; 10 (5%) employed longitudinal (including repeated cross‐sectional) data from nationally representative studies [15,17,140–146]; and 42 (23%) retrospectively assessed individual‐level data […”
Section: Resultsmentioning
confidence: 99%
“…One study from Becker et al [34] found that reporting past-year NMPOU was significantly associated with reporting symptoms of panic and phobia among National Survey on Drug Use and Health respondents (n = 6879; both adjusted odds ratios = 1.2, P < 0.05). Ten studies (5%) assessed the relationship between NMPOU and anxiety, with 7 (70%) identifying a significant association [7,33,112,125,128,136,142], two studies (20%) reporting a null finding [43,122] and one (10%) limited to reporting on the prevalence of generalised anxiety disorder (i.e. 14%) among individuals engaged in NMPOU [77].…”
Section: B15-b24: Viral Hepatitis (Hepatitis B and C) And Hiv Studies...mentioning
confidence: 99%